Economic perspectives on DEA - Finn R. Førsund (University of Oslo, Department of Economics, 2015)
Research on productive efficiency at the firm level has developed as an important and active strand of research the last decades, both within operations research, management science and economics. However, the interests pursued within the fields have had some differences regarding sound theoretical foundations. The perspective within economics is highlighted and a critique of some research directions judged as unfortunate is offered.
Keywords: C61; D24; 330; efficiency measures; data envelopment analysis; shadow prices; weight restrictions; cross-efficiency